2001
DOI: 10.1074/jbc.m106223200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Ym2 Lectin-binding Protein Is Dependent on Interleukin (IL)-4 and IL-13 Signal Transduction

Abstract: Asthma pathophysiology is intimately regulated by CD4؉ Th2 lymphocytes and the cytokines interleukin (IL)-4 and IL-13. However, the mechanisms by which these cytokines promote disease have not been fully elucidated. In order to identify novel molecular mediators of allergy, a comparison was made of the bronchoalveolar lavage, which demonstrated that the Ym2 protein was abundantly up-regulated in the lung during the development of allergy. Low levels of the Ym1 isomer were also detected. Importantly, neither Ym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
161
3
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(175 citation statements)
references
References 40 publications
9
161
3
2
Order By: Relevance
“…Finally, expression of Ym2, closely related to Ym1, depends upon IL-4R␣ signal transduction (94,95). We show that in the absence of IL-13, Ym1, FIZZ1, and acidic chitinase mRNA are significantly reduced, and their expression correlates with a Th2-polarized phenotype (96,97). The dramatic induction of these genes between days 8 and 14 indicates they may be involved in tissue repair or may simply reflect an increase in the alternatively activated macrophage population.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, expression of Ym2, closely related to Ym1, depends upon IL-4R␣ signal transduction (94,95). We show that in the absence of IL-13, Ym1, FIZZ1, and acidic chitinase mRNA are significantly reduced, and their expression correlates with a Th2-polarized phenotype (96,97). The dramatic induction of these genes between days 8 and 14 indicates they may be involved in tissue repair or may simply reflect an increase in the alternatively activated macrophage population.…”
Section: Discussionmentioning
confidence: 96%
“…[23][24][25] Chitinase-like proteins YM-1 and YM-2 had been found in crystal forms in the lungs in mouse models of asthma. 23,24 Crystal particles were readily appreciated in the BAL fluid and in the lungs of SHIP-1 −/− mice (see Fig E6, A, in the Online Repository at www.jacionline.org). RT-PCR confirmed that acidic mammalian chitinase (AMCase), YM-1, and YM-2, but not chitotriosidase, were upregulated in the lungs of SHIP-1 −/− mice (Fig E6, B).…”
Section: Discussionmentioning
confidence: 99%
“…Both Ym1 and Ym2 proteins, related members of the chitinase family, are dramatically upregulated in the presence of Th2 inflammation (43,52,60). To determine whether the staining pattern for AMCase is typical of all members of the chitinase family, we performed in situ hybridization for Ym1 in ovalbumin-challenged and IL-13 transgenic mice ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…AMCase has also been suggested to be involved in remodeling of the extracellular matrix (43). Ym1 has been associated with alternatively activated macrophages and has weakly active eosinophil recruiting activity (38,52). Ym1 binds saccharides with a free amine group, including n-glucosamine and their oligosaccharides, as well as heparin, suggesting a role in binding to both extracellular matrix and parasite eggs (8,49).…”
Section: Discussionmentioning
confidence: 99%